دور أستاذ التربية البيدنية والرياضية في انتقاء وتوجيه التلاميذ لمختلف الأنشطة الريلضية - ولد ملحة, زكرياء; بن فريحة, يونس (Institut d’Éducation Physique et Sportive mostaganem 2022/2023, 2023)
Study Title: The Role of Physical Education and Sports Teachers in Selecting and Guiding Students for Various Sports Activities. The study aims to identify the idea and methodology of selecting and guiding gifted students at the intermediate level for various activities that suit them, by the supervising teachers. The assumption of the study is that physical education teachers have a role in selecting and guiding students for various sports activities. The sample consisted of 28 physical education teachers at the intermediate education stage, distributed among 12 intermediate schools in the provinces of Mascara and Relizane. The selection was made randomly. The tool used was the questionnaire method. The most important conclusion is that the experience and scientific competence of the teacher play an important role in selecting and guiding students. The most important suggestion is to follow up on gifted students and supervise them to ensure their continued progress and provide diverse educational programs that cater to the students' needs and encourage them to develop their skills and discover their talents.
LEPS-2023-8
Keywords: Selection and guidance of students - average students - gifted students - sports activities The sample was 28 teachers in physical education for the intermediate education stage distributed